Public Procurements Performance Measurement in Indonesian FDA According to Head of National Public Procurement Agency’s Circular Letter Number 2 of Year 2021 Concerning Procurement Governance Index - Murti, Dyah Meita Retno; Putro, Utomo Sarjono (Budapest International Research and Critics University, 2021)
Public procurement defined as purchasing process of goods, services and works, by governments. Government as public procurement entity are expected to conduct the process under highly standards, to report it transparently and to ensure its efficiency and effectiveness, under value of money principle. In accordance with this issue, Indonesia governments continuously develop public procurement system, led by The National Public Procurement Agency. E-procurement system was built, transactional covering the whole cycle, and public procurement regulations are revised as an adaptation of national economic development. In order to evaluate governance of procurement process, The Public Procurement Policy Agency develop set of performance indicator to reflect internal procurement governance of public procurement accounts, as issued in Head of National Public Procurement Agency’s Circular Letter Number 2 Year 2021. This indicator also acts as a measurement aspect of the bureaucratic reform that must be implemented by government ministries/institutions, including The Indonesia Food and Drug Agency. The purpose of this study is to capture The Indonesia Food and Drug Agency procurements governance according to Head of Public Procurement Policy Agency’s Circular Letter Number 2 Year 2021. Considering that the indicator has just implemented in 2021, there would be some internal hindrance that potentially influence the performance of public procurements which may affect its continuity. This condition can cause delays in the utilization of output so that the principles of efficiency and effectiveness can’t be achieved. 25 internal public procurements practitioners and stakeholder participated in this research. 25 potential problems were identified and analyzed under Kepner-Tregoe situation appraisal. The result of this research expected to be useful to determine which public procurement strategies should be implemented to overcome obstacles.